Hodgkin lymphoma in pregnant women: patient management - Yu.E. Dobrokhotova; S.Zh. Danelyan; E.I. Borovkova; E.A. Nagaytseva; D.Kh. Sarakhova; I.M. Borovkov; M.S. Guseva (LCC «Medicine-Inform», 2023)
Yu.E. Dobrokhotova1, S.Zh. Danelian2, E.I. Borovkova1, E.A. Nagaytseva2, D.Kh. Sarakhova2, I.M. Borovkov3, M.S. Guseva4 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Moscow Multidisciplinary Clinical Center "Kommunarka", Moscow, Russian Federation 3N.N. Blokhin National Medical Research Center of Oncology, Moscow, Russian Federation 4V.V. Veresaev City Clinical Hospital, Moscow, Russian Federation Hodgkin lymphoma (HL) is a B-cell malignant lymphoproliferative disease occurring with a prevalence of 2.2 cases per 100,000 population per year, more commonly in women, with a peak incidence in the range of 16-35 years. The most common type in pregnant women is classical HL, diagnosed with a prevalence of 1:1000-1:6000. The authors present a literature review on pregnancy in patients with HL, as well as describe own experience of delivery in 20 patients with HL, of whom 16 (80%) had the disease in stable remission, and 4 (20%) were first diagnosed with HL during pregnancy. The pregnancy course was complicated by preeclampsia in 4 (20%) patients, threatened preterm labor in 5 (25%) and anemia in 6 (30%). Delivery at term occurred in 18 (90%), by cesarean section in 4 (20%). Keywords: Hodgkin lymphoma, lymphogranulomatosis, pregnancy, lymphadenopathy, polychemotherapy, radiation therapy. For citation: Dobrokhotova Yu.E., Danelian S.Zh., Borovkova E.I., Nagaytseva E.A., Sarakhova D.Kh., Borovkov I.M., Guseva M.S. Hodgkin lymphoma in pregnant women: patient management. Russian Journal of Woman and Child Health. 2023;6(4):391-398 (in Russ.). DOI: 10.32364/2618-8430-2023-6-4-11.